Sustainable Electrical Discharge Machining (EDM) Of Inconel 718 When Using RBD Palm Oil Based Dielectric Fluid - Ahmad, Said; Mohan, Vellmurugan; Lajis, Mohd Amri; Ho, Fu Haw; Kiow, Lee Woon; Talib, Norfazillah; Abdul Haq, Reazul Haq (Journal of Sustainable Manufacturing in Transportation, 2024)
Electrical Discharge Machining (EDM) involves the discharge of a series of discrete sparks from a high-voltage electrical arc between the metal and the workpiece, therefore removing the metal. This experimental research aims to evaluate the material removal rate (MRR), electrode wear rate (EWR), and surface roughness (Ra) of an Inconel 718 and a copper (Cu) electrode while using a sustainable electrical discharge machining (EDM) method with the usage of either a modified bio-degradable or traditional dielectric fluid. RBD palm oil has been trans-esterified to achieve the same viscosity concentration as kerosene fluids. In this study, the influence of peak current from 6A to 12A and Pulse duration from 50?s to 150?s on the machinability performance were investigated. Scanning Electron Microscope (SEM) was used to examine the surface topography of Inconel 718 and electrode surface morphology. The result shows that at highest Ip=12A and the lowest ton=150?s yield the highest MRR for those RBD palm oil, modified RBD, and kerosene dielectric fluid. The improvement of MRR for RBD palm oil and modified RBD as dielectric fluid is about 46.82% and a decrement of 8.89% when compared to kerosene at the same parameter settings. Meanwhile, machining by using RBD palm oil, modified RBD, and kerosene at Ip =6A and ton =150µs yields the lowest EWR and Ra respectively. However, the value of EWR and Ra for RBD palm is slightly higher compared to kerosene and modified RBD. In the case of machinability, RBD palm oil shows the best results in the EDM machining of Inconel 718.